Peran Modal Sosial Dalam Penguatan Kapasitas Kelompok Tani Nirati Binaan PT Arutmin NPLCT - Wulandari, Indah; Izana, Nyimas Nadya; Kartika, Ayu (Prodi Sosiologi Universitas Mataram, 2025)
The farmer group development program is a form of corporate social responsibility (CSR) implementation that seeks to improve the social and economic capacity of the community. PT Arutmin NPLCT implements a development program for the Nirati farmer group in its operational area as part of its sustainable community development strategy. This study aims to analyze the social capital formed within the Nirati farmer group, describe the forms of empowerment provided by the company, and examine the relationship between the two in improving the group's capacity. This study uses a qualitative approach with a case study through in-depth interviews, observation, and documentation studies. Informants consisted of the chairperson and members of the Nirati farmer group, PT Arutmin's CSR facilitators, and relevant village officials. The results of the study show that social capital, in the form of trust, norms, and social networks, plays a role in sustaining the coaching program. The empowerment program, which includes technical training, facility support, institutional strengthening, and intensive assistance, provides opportunities for capacity development. However, collective participation remains limited, activities are mostly individual, and a majority of members are not consistently engaged. These results highlight the challenges of translating empowerment initiatives into sustained collective action, emphasizing the role of social capital in supporting gradual improvements.